If Pigs Could Fly... and Other Deep Thoughts - Bruce Lansky (India Meadowbrook Press, 2006)
"If Pigs Could Fly and Other Deep Thoughts" is a collection of Bruce Lansky's own hilarious poems about everything kids are concerned with, including: smelly diapers, chubby relatives, toothless grandmas, dirty socks, impolite dogs, burping babies, bad hair days and more. The poems in this book have been tested on over 1,000 schoolchildren and their teachers so that only the most giggle-packed poems are included.
Keywords: Poetry -- Poetry